The Relationship Between Talent Management Practices and Retention of Generation ‘Y’ Employees: Mediating Role of Competency Development - SH. M. Fakhr-e-Alam Siddique; Hammad Zafar; Ramzan Ali Balouch , (Dialogue Social Science Review (DSSR), 2024)
The workforce of today is highly diverse due to the notable behavioral and other distinctions that exist among workers. Businesses operating in a competitive economy face challenges in retaining younger and competent people. Employers must use staff development strategies if they want to keep Generation Y workers. The aim of this research is to investigate relationship between talent management practices, including knowledge sharing, social media, strategic leadership practices, mentoring, and intension of generation Y employees to remain in present positions. Moreover, the mediating role of competency development will be examined in order to strengthen this relationship. The more knowledge assets are shared inside the company, the more employee competencies will be improved. An organization must use learning and development strategies to elicit emotional attachment from Gen Y workers. Effectively managing talent, organizations need integrate information sharing, social media, strategic leadership, and mentoring. Employees from Generation Y become more committed as a result of competency development, and they then intend to stick around. The framework provides a way to design a retention strategy for every generation. A total of 350 generation Y employees engaged in the survey. The information was assessed using the PLS-SEM model using SmartPLS-4 software. The results indicate, while knowledge exchange does not significantly affect the intention to stay, social media, strategic leadership, and mentoring are examples of TM practices that positively influence generation Y employees’ inclination to stick around. Competency development acts as a mediator in the link between social media, Knowledge sharing, strategic leadership, mentoring and intention to stay. As a mediator in the interaction between these variables / construct is not very effective.